2021
DOI: 10.1016/s2214-109x(21)00039-5
|View full text |Cite
|
Sign up to set email alerts
|

Multimonth dispensing of up to 6 months of antiretroviral therapy in Malawi and Zambia (INTERVAL): a cluster-randomised, non-blinded, non-inferiority trial

Abstract: Background Facility-based, multimonth dispensing of antiretroviral therapy (ART) for HIV could reduce burdens on patients and providers and improve retention in care. We assessed whether 6-monthly ART dispensing was non-inferior to standard of care and 3-monthly ART dispensing.Methods We did a pragmatic, cluster-randomised, unblinded, non-inferiority trial (INTERVAL) at 30 health facilities in Malawi and Zambia. Eligible participants were aged 18 years or older, HIV-positive, and were clinically stable on ART.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…All were sponsored by the U.S. Agency for International Development and the U.S. President’s Emergency Program for AIDS Relief (PEPFAR) under the EQUIP Health project. Clinical outcomes and costs of these studies have previously been reported 5 11 . All utilized primary healthcare clinics and/or hospital outpatient clinics to implement and evaluate between three and six differentiated models of delivery of antiretroviral therapy for stable, adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…All were sponsored by the U.S. Agency for International Development and the U.S. President’s Emergency Program for AIDS Relief (PEPFAR) under the EQUIP Health project. Clinical outcomes and costs of these studies have previously been reported 5 11 . All utilized primary healthcare clinics and/or hospital outpatient clinics to implement and evaluate between three and six differentiated models of delivery of antiretroviral therapy for stable, adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…The overall retention in care was lower than that of patients with both controlled HIV and hypertension at baseline, which was at 98%. However, the retention in our cohort was higher than that in the general HIV population of about 76% [ 26 ] and 86% for stable patients [ 27 ]. Integrated MMD of both hypertension and ART medications in our cohort reduced the frequency of clinic visits, transportation costs and minimized patient loss to follow-up and improved retention in care as well as HIV and hypertension control.…”
Section: Discussionmentioning
confidence: 57%
“…This analysis is thus not reflective of the total scope of 4‐ to 6‐month dispensing during the COVID‐19 pandemic, but of new DSD enrolees alone. It is possible that new DSD enrolees receive ≤3‐month dispensing at first, but then switched to 4‐ to 6‐month dispensing during the pandemic period [ 15 ].…”
Section: Resultsmentioning
confidence: 99%